Enzymes in Fish and Seafood Processing - Fernandes, Pedro (Frontiers in Bioengineering and Biotechnology, 2016)
Enzymes have been used for the production and processing of fish and seafood for several centuries in an empirical manner. In recent decades a growing trend towards a rational and controlled application of enzymes for such goals has emerged. Underlying such pattern are among others, the increasingly wider array of enzyme activities and enzyme sources, improved enzyme formulations and enhanced requirements for cost-effective and environmentally friendly processes. The better use of enzyme action in fish and seafood related application has had a significant impact in fish related industry. Thus, new products have surfaced, product quality has been improved, more sustainable processes have been developed and innovative and reliable analytical techniques have been implemented. Recent development in these fields are presented and discussed and prospective developments are suggested.